Human response to eVTOL drone sound: an online listening experiment exploring the effects of operational and contextual factors - Woodcock, James; Thomas, Adam; Hiller, David; Maldonado, Ana Luisa Pereira; McLeod, Laura; Sharp, Calum; Smith, Fiona (Frontiers in Acoustics, 2025)
IntroductionProject CAELUS is developing the United Kingdom's first national distribution network using drones to transport vital medical supplies throughout Scotland. Noise is a major barrier to public acceptance of drone networks, yet empirical data on the human response to drones used in a medical delivery context remains limited. This study addresses that gap by investigating the annoyance response to sounds from the eVTOL medical delivery drone used in Project CAELUS.MethodsAn online listening experiment was conducted to assess annoyance related to overflight (N – 425) and take-off (N – 278) operations. The experiment examined the effects of listener–drone distance, ambient soundscape (remote rural, rural village, urban), and contextual framing (medical delivery vs. no context) on annoyance. Data were analysed using aligned rank transform ANOVAs to test for main effects and interactions for each factor.ResultsAligned rank transform ANOVAs revealed significant effects of listener–drone distance, ambient soundscape, and contextual framing on annoyance (p < 0.01 for all three factors). Annoyance decreased with increasing distance from the drone and was higher in quieter ambient soundscapes. Providing contextual information about the medical use of the drone significantly reduced annoyance.DiscussionFindings indicate that both acoustic and non-acoustic factors influence perceived annoyance from drone operations. In particular, contextual information about medical use reduced annoyance, suggesting that effective community engagement may improve public acceptance of drone networks.